Preparation and use methods of silicon dioxide modified copper-zinc-aluminum catalyst

By introducing silica into the copper-zinc-aluminum catalyst, the catalyst interaction and the formation of Cuδ+ species are strengthened, and the low conversion and instability of existing catalysts are solved, achieving higher methanol selectivity and catalyst stability.

CN119633831AActive Publication Date: 2025-03-18ACRE COKING & REFRACTORY ENG CONSULTING CORP DALIAN MCC +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411672809.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing catalysts for synthesis of methanol by carbon dioxide hydrogenation have problems such as low CO2 conversion, poor methanol selectivity and unstable catalysts.

Method used

By introducing silica species during the synthesis of copper-zinc-aluminum catalysts, a silica-modified copper-zinc-aluminum catalyst was prepared, which strengthened the interaction between metal copper particles and the support, promoted the generation of Cuδ+ species, thereby improving the stability of the catalyst and methanol selectivity.

Benefits of technology

It significantly improves the stability and methanol selectivity of the catalyst, enhances the conversion rate to CO2, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633831A_ABST
    Figure CN119633831A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation and use method of a silicon dioxide modified copper-zinc-aluminum catalyst. The preparation method comprises the following steps: dissolving a copper salt, a zinc salt and an aluminum salt in deionized water to obtain a solution A; dissolving sodium carbonate in deionized water to obtain a solution B; dissolving silicon salt or organic silicon in deionized water or absolute ethyl alcohol to obtain a solution C; dropwise adding the solution A, the solution B and the solution C into a beaker containing deionized water, and adjusting the dropwise adding speed of the solution B to keep the pH value of the reaction solution in an alkaline range; and aging the precipitate obtained by the reaction, washing, carrying out suction filtration, drying, and roasting to obtain the copper-zinc-aluminum-silicon catalyst. The molar percentage contents of copper, zinc, aluminum and silicon are 20%-50%, 10%-40%, 10%-40% and 10%-30% respectively. The anti-sintering resistance of the catalyst is effectively enhanced, the electronic property of Cu nanoparticles in the catalyst is regulated and controlled, and generation of more Cu delta + species on the catalyst is promoted, so that reverse water gas, methanol decomposition and other side reactions are inhibited, the stability of the catalyst is greatly improved, and the methanol selectivity is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technology of synthesizing methanol by hydrogenating carbon dioxide, and in particular relates to a preparation and use method of a silicon dioxide-modified copper-zinc-aluminum catalyst for preparing methanol by hydrogenating CO2. Background Art

[0002] Carbon dioxide is a greenhouse gas and is considered to be an important cause of global warming. How to efficiently utilize carbon dioxide and convert it into valuable energy and chemical products has become a hot topic and difficulty in research. In addition to its role as a greenhouse gas, carbon dioxide is also a potential industrial raw material with broad application prospects. Carbon dioxide can be converted into methanol through catalytic hydrogenation technology. Methanol is a high-value-added chemical that can be directly used as a fuel, solvent, antifreeze, etc. It is also an important chemical intermediate that can be used to synthesize a variety of organic products such as formaldehyde, acetic acid, methyl chloride, methylamine, dimethyl sulfate, etc. Driven by environmental protection factors and attracted by market prospects, companies and scientific research institutions in many countries are actively developing and constructing carbon dioxide hydrogenation to methanol projects. These include Denmark's Topsoe, Japan's Kansai Electric Power Company and Mitsui Chemicals, Norway's Iceland, and Germany's Lurgi. By converting carbon dioxide into valuable products, it can not only reduce greenhouse gas emissions and resource consumption, but also promote the development of sustainable development and environmentally friendly industries. Therefore, strengthening the efficient utilization and conversion of carbon dioxide has become an important research direction worldwide and has great potential and market prospects in the field of energy and chemical industry.

[0003] At present, the development of catalysts for the synthesis of methanol from the hydrogenation of carbon dioxide is not yet mature, and most of the existing processes are achieved by improving the catalysts used for the hydrogenation of carbon monoxide to methanol. Related research mainly focuses on the study of reaction mechanism, the selection of active components and carriers, and the effects of different preparation methods and reaction conditions on catalyst performance. However, due to the limitations of thermodynamic equilibrium, traditional copper-zinc-aluminum methanol catalysts have disadvantages such as low CO2 conversion rate, poor methanol selectivity and catalyst instability. In order to overcome these problems, modern research pays more attention to the design and development of new catalysts. For example, in view of the special requirements under the conditions of CO2 hydrogenation reaction, it is possible to consider introducing new catalysts or adjusting the catalyst structure to improve the activity and selectivity of the catalyst. In addition, the performance of the catalyst can also be improved by improving the catalyst preparation method, optimizing the reaction conditions, and exploring new carrier materials. In view of the problem of catalyst instability, the life and stability of the catalyst can be studied, and effective regeneration and repair methods can be explored to extend the service life of the catalyst. In short, the research and development of catalysts for the hydrogenation of carbon dioxide to methanol is of great significance in reducing greenhouse gas emissions, achieving efficient resource utilization and promoting sustainable development. Future research should continue to focus on improving the activity and selectivity of the catalyst, solving the problems of catalyst stability and regeneration, so as to achieve the goal of efficient conversion of CO2 to methanol.

[0004] Therefore, in order to achieve the sustainable development of efficient carbon dioxide hydrogenation to methanol technology, it is of great significance to develop efficient carbon dioxide hydrogenation to methanol catalysts. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing and using a silica-modified copper-zinc-aluminum catalyst for hydrogenating CO2 to methanol.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The preparation and use method of the silica-modified copper-zinc-aluminum catalyst includes the following specific contents:

[0008] Take appropriate amounts of copper salt, zinc salt and aluminum salt, and dissolve them in deionized water to obtain solution A; take appropriate amount of sodium carbonate, and dissolve it in deionized water to obtain solution B; take appropriate amount of silicon salt or organic silicon, and dissolve it in deionized water or anhydrous ethanol to obtain solution C; under stirring conditions of 20 to 80° C., drop solution A, solution B and solution C into a beaker containing deionized water, and keep the pH value of the reaction solution in an alkaline range by adjusting the dropping speed of solution B;

[0009] The precipitate obtained by the reaction is aged for 2 to 24 hours, washed with deionized water, filtered, dried and calcined to obtain a copper-zinc-aluminum-silicon catalyst; the molar percentages of copper, zinc, aluminum and silicon in the copper-zinc-aluminum-silicon catalyst are 20% to 50%, 10% to 40%, 10% to 40% and 10% to 30% respectively.

[0010] The copper salt, zinc salt and aluminum salt are one or more of nitrates, sulfates and chlorides corresponding to the elements copper, zinc and aluminum, respectively.

[0011] The silicon salt or organosilicon is one or more of sodium silicate, ethyl orthosilicate, dimethyldiethoxysilane and phenyltriethoxysilane.

[0012] The stirring speed is 200-2000 rpm, the dripping flow rates of solution A and solution C are both 1-20 mL / min, the temperature is controlled at 60-180° C. and the time is 4-48 h during drying; the calcination is carried out in a muffle furnace with air passing through, the temperature is controlled at 300-700° C. and the time is 2-12 h.

[0013] The method for using a silica-modified copper-zinc-aluminum catalyst in catalyzing CO2 hydrogenation to produce methanol, wherein the silica-modified copper-zinc-aluminum catalyst is prepared by a preparation method of a silica-modified copper-zinc-aluminum catalyst for CO2 hydrogenation to produce methanol, specifically comprising:

[0014] The silica-modified copper-zinc-aluminum catalyst is loaded into a high-pressure fixed-bed reactor, reduced by a mixture of hydrogen and nitrogen with a hydrogen concentration of 5 to 99 mol% at 210 to 400°C, and then heated at a temperature of 200 to 300°C, a pressure of 1 to 9 MPa, and a space velocity of 500 to 50000 mL / (g cat ·h), introducing reaction gas to realize catalytic hydrogenation to produce methanol; the molar ratio of H2 to CO2 in the reaction gas is (1-10):1.

[0015] If it is necessary to add CO to the reaction gas, the molar percentage of CO to the reaction gas is 0-10%.

[0016] Description of the invention principle:

[0017] The present invention introduces silicon species in situ during the synthesis process of the copper-zinc-aluminum catalyst, and finally obtains the silicon dioxide modified copper-zinc-aluminum catalyst.

[0018] A series of catalysts have been prepared for the hydrogenation of CO2 to methanol. Among them, supported copper nanoparticles are favored due to their high activity for the activation and conversion of CO2. However, due to the low Tammann temperature of copper, these copper nanoparticles are prone to sintering into larger particles, resulting in the loss of active sites. For example, the widely studied Cu / ZnO / Al2O3 catalysts show a continuous decline in activity during the CO2 hydrogenation process. In order to improve the sintering resistance of Cu nanoparticles, various metal oxides such as ZrO x (CN118002137A and CN103272607A), GaO x (CN116899577A), LaO x (Applied catalysisA:General.2013,468:442-452.) and CeO x (CN117101669A) etc. However, due to the enhancement of the side reaction of the water gas reverse shift, in many cases, the carbon dioxide conversion rate is low and the selectivity of the target product methanol is reduced.

[0019] In order to overcome this limitation, silica carriers are widely used to modify Cu catalysts to improve the performance of catalysts in methanol synthesis. Patent CN105521775B proposes a method for synthesizing a Cu-based catalyst by mixing gas-phase SiO2 and silica sol SiO2 to prepare a slurry, and synthesizing the SiO2 carrier by centrifugal spray drying (wind temperature condition is 300°C), and preparing SiO2 modified Cu-based catalyst by ammonia evaporation method. The prepared catalyst has high metal dispersion, large specific surface area and excellent anti-wear performance, thereby showing high reaction activity and methanol synthesis performance. However, in this synthesis method, the preparation steps of SiO2 carrier are complicated and the required preparation temperature is high, which is not conducive to wide application. Our previous patent CN116393160A proposes a method for preparing a copper-zinc-aluminum-silica molecular sieve composite catalyst, using a solid phase synthesis method to prepare a hydrophobic or hydrophilic SiO2 molecular sieve, and physically mixing and filling the copper-zinc-aluminum catalyst with the SiO2 molecular sieve to form a composite catalyst, which can efficiently catalyze CO2 to methanol. The addition of SiO2 molecular sieves in this process can effectively reduce the concentration of H2O on the catalyst surface, improve catalyst stability and methanol synthesis performance. However, the synthesis process of SiO2 molecular sieves requires the use of raw materials such as organic silane, which is costly. At the same time, SiO2 and copper-zinc-aluminum catalysts are only physically mixed, which may lead to weak interaction between the two, and the catalytic methanol synthesis performance cannot be optimized.

[0020] In summary, we have developed a Cu / ZnO / Al2O3 catalyst modulated by silica (Cu / ZnO / Al2O3 / SiO2, CuZnAlSi). Compared with the traditional Cu / ZnO / Al2O3 catalyst, there is a strong interaction between silica and Cu nanoparticles on this catalyst, which shows stronger sintering resistance in CO2 hydrogenation to methanol. In addition, silica electronically regulates Cu nanoparticles, resulting in more Cu on the catalyst. δ+ Species. Due to Cu δ+ The species is mainly responsible for stabilizing the CH3O* intermediate and preventing it from decomposing to form the byproduct CO, thereby improving the selectivity of methanol. The results show that the methanol selectivity is significantly improved compared with the traditional Cu / ZnO / Al2O3 catalyst.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) Due to the low Tamman temperature of copper, sintering of metallic copper particles is likely to occur during the reaction, which in turn leads to the deactivation of the conventional CuZnAl methanol catalyst. The present invention strengthens the interaction between metallic copper particles and the carrier by introducing silicon dioxide species, thereby inhibiting their migration and agglomeration during the reaction, thereby improving the stability of the catalyst.

[0023] 2) Due to the presence of a large amount of Cu on the traditional copper-zinc-aluminum methanol catalyst 0 Species, resulting in severe reverse water gas (H2+CO2→CO+H2O) and methanol decomposition reaction (CH3OH→CO+2H2), thereby causing a large amount of CO by-products. The present invention promotes more Cu on the catalyst by introducing silica species. δ+ The generation of species is inhibited, thereby suppressing the side reactions such as reverse water gas and methanol decomposition, and achieving an improvement in the methanol selectivity on the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the in-situ reduction X-ray photoelectron spectroscopy (XPS) of the CuZnAl-1 catalyst of Example 9.

[0025] Figure 2 This is the in-situ reduction X-ray photoelectron spectroscopy (XPS) of the CuZnAlSi catalyst of Example 9.

[0026] Figure 3 This is the carbon monoxide adsorption infrared spectrum of the CuZnAl-1 catalyst of Example 9.

[0027] Figure 4 This is the carbon monoxide adsorption infrared spectrum of the CuZnAlSi catalyst of Example 9. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the specific implementation methods of the present invention are further described below in conjunction with embodiments. The following embodiments are used to specifically illustrate the contents of the present invention. These embodiments are only general descriptions of the contents of the present invention and do not limit the contents of the present invention.

[0029] Example 1: Application of silica-modified copper-zinc-aluminum catalyst in carbon dioxide hydrogenation.

[0030] (1) Synthetic copper-zinc-aluminum catalyst comparison sample:

[0031] (1.1) The CuZnAl-1 catalyst was synthesized by coprecipitation. 12.05 g (0.050 mol) of copper nitrate trihydrate, 10.40 g (0.035 mol) of zinc nitrate hexahydrate and 5.63 g (0.015 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. The mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted to keep the pH of the liquid in the beaker in the alkaline range. After aging the obtained precipitate for 12 h, it was washed with deionized water, filtered 6 times, and dried at 100 °C for 12 h. The dried product was placed in a muffle furnace and calcined at 500 °C for 4 h in air to obtain the CuZnAl-1 catalyst. In the catalyst, the molar percentages of copper, zinc and aluminum are 50%, 35% and 15% respectively.

[0032] (1.2) CuZnAl-2 catalyst was synthesized by coprecipitation. 12.05 g (0.050 mol) of copper nitrate trihydrate, 10.40 g (0.035 mol) of zinc nitrate hexahydrate and 5.63 g (0.015 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. Aqueous solution A and aqueous solution B were simultaneously dripped into a beaker containing 200 mL of deionized water, and the temperature was kept at 20 °C and the stirring speed was kept at 200 rpm. The dripping flow rate of solution A was controlled to be 1 mL / min, and the dripping speed of aqueous solution B was adjusted to keep the pH of the liquid in the beaker in the alkaline range. After aging the obtained precipitate for 4 h, it was washed with deionized water, filtered 6 times, and dried at 60 °C for 48 h. The dried product was placed in a muffle furnace and calcined at 300° C. for 12 hours in air to obtain a copper-zinc-aluminum catalyst CuZnAl-2, in which the molar percentages of copper, zinc and aluminum were 50%, 35% and 15% respectively.

[0033] (2) Synthesis of silica-modified copper-zinc-aluminum catalyst:

[0034] (2.1) CuZnAlSi-1 catalyst was synthesized by coprecipitation. 12.05 g (0.050 mol) of copper nitrate trihydrate, 7.43 g (0.025 mol) of zinc nitrate hexahydrate and 3.62 g (0.015 mol) of aluminum chloride hexahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.22 g (0.010 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the temperature was kept at 20 °C and the stirring speed was kept at 200 rpm. The dripping flow rate of solution A was controlled to be 1 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 4 hours, washed with deionized water, filtered 6 times, and dried at 60°C for 48 hours. The dried product was placed in a muffle furnace and calcined at 300°C for 12 hours in air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi-1. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 50%, 25%, 15%, and 10%, respectively.

[0035] (2.2) CuZnAlSi-2 catalyst was synthesized by coprecipitation. 5.00 g (0.020 mol) of copper sulfate pentahydrate, 11.88 g (0.040 mol) of zinc nitrate hexahydrate and 11.25 g (0.030 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.22 g (0.010 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the temperature was kept at 80 °C and the stirring speed was kept at 2000 rpm. The dripping flow rate of solution A was controlled to be 20 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 48 hours, washed with deionized water, filtered 6 times, and dried at 180°C for 4 hours. The dried product was placed in a muffle furnace and calcined at 700°C for 2 hours with air to obtain a copper-zinc-aluminum catalyst silica-modified CuZnAlSi-2. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 20%, 40%, 30%, and 10%, respectively.

[0036] (2.3) CuZnAlSi-3 catalyst was synthesized by coprecipitation. 9.64 g (0.040 mol) of copper nitrate trihydrate, 2.97 g (0.010 mol) of zinc nitrate hexahydrate and 15.00 g (0.040 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.22 g (0.010 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the temperature was kept at 20 °C and the stirring speed was kept at 200 rpm. The dripping flow rate of solution A was controlled to be 1 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 4 hours, washed with deionized water, filtered 6 times, and dried at 60°C for 48 hours. The dried product was placed in a muffle furnace and calcined at 300°C for 12 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi-3. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 40%, 10%, 40%, and 10%, respectively.

[0037] (2.4) CuZnAlSi-4 catalyst was synthesized by coprecipitation. 9.64 g (0.040 mol) of copper nitrate trihydrate, 5.94 g (0.020 mol) of zinc nitrate hexahydrate and 11.25 g (0.030 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.22 g (0.010 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 20 °C and stirred at 200 rpm. The dripping flow rate of solution A was controlled to be 1 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 4 hours, washed with deionized water, filtered 6 times, and dried at 60°C for 48 hours. The dried product was placed in a muffle furnace and calcined at 300°C for 12 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi-4. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 50%, 30%, 10%, and 10%, respectively.

[0038] The catalytic reaction performance of the carbon dioxide hydrogenation reaction was tested on a fixed bed reactor. The test steps are as follows:

[0039] (1) The activity of the previously prepared CuZnAl-1 and CuZnAl-2 catalysts and four silica-modified CuZnAl catalysts (CuZnAlSi) for CO2 hydrogenation to methanol was evaluated. First, 0.5 g of catalyst particles (20-40 mesh) and 2.0 g of inert quartz sand (20-40 mesh) were physically shaken and mixed, and then poured into a stainless steel reactor for loading. Quartz wool was used to fill the two ends to maintain the bed height, and a fixed bed reactor was assembled.

[0040] (2) Using a space velocity of 3000 mL / (g cat h) reducing the catalyst at 400° C. for 6 h using a mixture of hydrogen and nitrogen with a hydrogen concentration of 5 mol %.

[0041] (3) A reaction gas having a molar ratio of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) of 72.0 / 24.0 / 4.0 was introduced into a high-pressure fixed-bed reactor, the catalyst bed temperature was controlled to be 240° C., the reaction pressure was 3.0 MPa, and the volumetric space velocity of the feed gas was 6000 mL / (g cat h).

[0042] Note: The reaction gas used here is pure CO2 / H2 / Ar, where Ar is used as an internal standard to assist in calculating the CO2 conversion rate. Because CO is generated during the reaction, it is necessary to add additional CO to the raw gas when simulating a cycle experiment. The following examples will list experiments with CO addition. The experimental results are shown in Table 1:

[0043] Table 1:

[0044]

[0045] 3MPa, 240℃, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4, reaction time is 40h.

[0046] It can be seen from the above test results that the introduction of silicon dioxide can improve the selectivity of methanol. The CO2 conversion rate of CuZnAlSi-1 is 15.4%, the methanol selectivity is 75.4%, and the methanol yield is 11.6%, which is the best performance among the four samples.

[0047] Example 2: Application of silica-modified copper-zinc-aluminum catalysts with different silicon contents in carbon dioxide hydrogenation.

[0048] (1) Synthesis of silica-modified copper-zinc-aluminum catalysts with different silicon contents:

[0049] (1.1) CuZnAlSi0.1 catalyst was synthesized by coprecipitation. 12.05 g (0.050 mol) of copper nitrate trihydrate, 7.43 g (0.025 mol) of zinc nitrate hexahydrate and 5.63 g (0.015 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.22 g (0.010 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.1. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 50%, 25%, 15%, and 10%, respectively.

[0050] (1.2) CuZnAlSi0.15 catalyst was synthesized by coprecipitation. 11.38 g (0.047 mol) of copper nitrate trihydrate, 7.01 g (0.024 mol) of zinc nitrate hexahydrate and 5.31 g (0.014 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.83 g (0.015 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.15. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 47%, 24%, 14%, and 15%, respectively.

[0051] (1.3) CuZnAlSi0.2 catalyst was synthesized by coprecipitation. 10.71 g (0.044 mol) of copper nitrate trihydrate, 6.60 g (0.022 mol) of zinc nitrate hexahydrate and 5.00 g (0.013 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 2.44 g (0.020 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.2. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 44.4%, 22.2%, 13.2%, and 20.2%, respectively.

[0052] (1.4) CuZnAlSi0.25 catalyst was synthesized by coprecipitation. 10.04 g (0.042 mol) of copper nitrate trihydrate, 6.19 g (0.021 mol) of zinc nitrate hexahydrate and 4.69 g (0.013 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 3.05 g (0.025 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.25. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 41.6%, 20.8%, 12.8%, and 24.8%, respectively.

[0053] (1.5) CuZnAlSi0.3 catalyst was synthesized by coprecipitation. 9.37 g (0.039 mol) of copper nitrate trihydrate, 5.78 g (0.019 mol) of zinc nitrate hexahydrate and 4.38 g (0.012 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 1.22 g (0.010 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.3. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 39%, 19%, 12%, and 30%, respectively.

[0054] The catalytic reaction performance of the carbon dioxide hydrogenation reaction was tested on a fixed bed reactor. The test steps are as follows:

[0055] (1) The activity of the previously prepared CuZnAl-1 catalyst and five silica-modified CuZnAl catalysts (CuZnAlSi) for CO2 hydrogenation to methanol was evaluated. First, 0.5 g of catalyst particles (20-40 mesh) and 2.0 g of inert quartz sand (20-40 mesh) were physically shaken and mixed, and then poured into a stainless steel reactor for loading. Quartz wool was used to fill the two ends to maintain the bed height, and a fixed bed reactor was assembled;

[0056] (2) Using a space velocity of 3000 mL / (g cat h) reducing the catalyst at 210° C. for 6 h using a mixture of hydrogen and nitrogen with a hydrogen concentration of 99 mol %.

[0057] (3) A reaction gas having a molar ratio of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) of 72.0 / 24.0 / 4.0 was introduced into a high-pressure fixed-bed reactor, the catalyst bed temperature was controlled to be 240° C., the reaction pressure was 3.0 MPa, and the volume space velocity of the feed gas was in the range of 6000 mL / (g cat h). The experimental results are shown in Table 2.

[0058] Table 2:

[0059]

[0060] 3MPa, 240℃, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4, and the operating time is 40h.

[0061] From the above test results, it can be seen that when the amount of silicon dioxide introduced on the CuZnAlSi catalyst is 20 mol%, the catalyst has the best performance, that is, the CO2 conversion rate on the CuZnAlSi0.2 catalyst is 14.5%, the methanol selectivity is 85.1%, and the methanol yield is 12.3%.

[0062] Example 3: Application of silica-modified copper-zinc-aluminum catalysts prepared from different silicon sources in carbon dioxide hydrogenation.

[0063] (1) Synthesis of silica-modified copper-zinc-aluminum catalysts prepared using different silicon sources:

[0064] (1.1) CuZnAlSi0.2-1 catalyst was synthesized by coprecipitation. 10.71 g (0.044 mol) of copper nitrate trihydrate, 6.60 g (0.022 mol) of zinc nitrate hexahydrate and 5.00 g (0.013 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 2.44 g (0.020 mol) of sodium silicate was dissolved in 200 mL of deionized water to obtain aqueous solution C. Aqueous solution A, aqueous solution B and aqueous solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.2. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 44.4%, 22.2%, 13.2%, and 20.2%, respectively.

[0065] (1.2) CuZnAlSi0.2-2 catalyst was synthesized by coprecipitation. 10.71 g (0.044 mol) of copper nitrate trihydrate, 6.60 g (0.022 mol) of zinc nitrate hexahydrate and 5.00 g (0.013 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 4.16 (0.020 mol) of tetraethyl orthosilicate was dissolved in 200 mL of anhydrous ethanol to obtain ethanol solution C. Aqueous solution A, aqueous solution B and ethanol solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.2. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 44.4%, 22.2%, 13.2%, and 20.2%, respectively.

[0066] (1.3) The CuZnAlSi0.2-3 catalyst was synthesized by coprecipitation. 10.71 g (0.044 mol) of copper nitrate trihydrate, 6.60 g (0.022 mol) of zinc nitrate hexahydrate and 5.00 g (0.013 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 2.96 g (0.020 mol) of dimethyldiethoxysilane was dissolved in 200 mL of anhydrous ethanol to obtain ethanol solution C. Aqueous solution A, aqueous solution B and ethanol solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.2. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 44.4%, 22.2%, 13.2%, and 20.2%, respectively.

[0067] (1.4) CuZnAlSi0.2-4 catalyst was synthesized by coprecipitation. 10.71 g (0.044 mol) of copper nitrate trihydrate, 6.60 g (0.022 mol) of zinc nitrate hexahydrate and 5.00 g (0.013 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. 4.80 g (0.020 mol) of phenyltriethoxysilane was dissolved in 200 mL of anhydrous ethanol to obtain ethanol solution C. Aqueous solution A, aqueous solution B and ethanol solution C were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A and solution C was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. The obtained precipitate was aged for 12 hours, washed with deionized water, filtered 6 times, and dried at 100°C for 12 hours. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours with air to obtain a silica-modified copper-zinc-aluminum catalyst CuZnAlSi0.2. The molar percentages of copper, zinc, aluminum, and silicon in the catalyst were 44.4%, 22.2%, 13.2%, and 20.2%, respectively.

[0068] The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor. The test steps for the catalytic reaction performance are as follows:

[0069] (1) The activity of four silica-modified CuZnAl catalysts (CuZnAlSi) prepared previously for CO2 hydrogenation to methanol was evaluated. First, 0.5 g of catalyst particles (20-40 mesh) and 2.0 g of inert quartz sand (20-40 mesh) were physically shaken and mixed, and then poured into a stainless steel reactor for loading. Quartz wool was used to fill the two ends to maintain the bed height, and a fixed bed reactor was assembled;

[0070] (2) Using a space velocity of 3000 mL / (g cat h) reducing the catalyst at 300° C. for 6 h using a mixture of hydrogen and nitrogen with a hydrogen concentration of 10 mol %.

[0071] (3) A reaction gas having a molar ratio of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) of 72.0 / 24.0 / 4.0 was introduced into a high-pressure fixed-bed reactor, the catalyst bed temperature was controlled to be 240° C., the reaction pressure was 3.0 MPa, and the volume space velocity of the feed gas was in the range of 6000 mL / (g cat h). The test results are shown in Table 3.

[0072] Table 3:

[0073]

[0074]

[0075] 3MPa, 240℃, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4, and the operating time is 40h.

[0076] From the test results of Example 3, it can be seen that the CuZnAlSi0.2 catalyst synthesized with Na2SiO3 as the silicon source has the best performance, achieving a CO2 conversion rate of 14.5%, a methanol selectivity of 85.1%, and a methanol yield of 12.3%. This is because organic silicon has a strong non-polarity and cannot be evenly dispersed in an aqueous solution, resulting in uneven distribution of Cu particles and silica carriers on the CuZnAlSi0.2 catalyst.

[0077] Example 4: Tests at different reaction temperatures.

[0078] The CuZnAlSi0.2 catalyst is the same as in Example 2. The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor, and the test steps for the catalytic reaction performance were as follows:

[0079] 0.5 g CuZnAlSi0.2 (20-40 mesh) and 2.0 g quartz sand (20-40 mesh) were physically mixed and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions of the catalyst were the same as those in Example 1. The reaction conditions were: a reaction gas of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) = 72.0 / 24.0 / 4.0, the catalyst bed temperature was controlled at 200°C, 220°C, 240°C, 260°C, 280°C, and 300°C, the reaction pressure was 3.0 MPa, and the volume space velocity range of the feed gas was 6000 mL / (g cat The experimental results are shown in Table 4.

[0080] Table 4:

[0081]

[0082] 3MPa, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4, and the operating time is 40h.

[0083] From the above test results, it can be seen that increasing the reaction temperature can increase the CO2 conversion rate of the CuZnAlSi0.2 catalyst, but it will also cause a decrease in methanol selectivity. For example, when the reaction temperature is 200°C, the CO2 conversion rate is only 6.6%, but the methanol selectivity is as high as 94.2%; when the reaction temperature rises to 300°C, although the CO2 conversion rate is also increased to 21.0%, the methanol selectivity drops to 42.8%. In general, when the reaction temperature is 240°C, the catalyst shows the best performance, making the CO2 conversion rate and methanol selectivity reach 14.5% and 85.1%, and the methanol yield is 12.3%.

[0084] Example 5: Tests under different reaction pressures.

[0085] The CuZnAlSi0.2 catalyst is the same as in Example 2. The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor, and the test steps for the catalytic reaction performance were as follows:

[0086] 0.5 g CuZnAlSi0.2 (20-40 mesh) and 2.0 g quartz sand (20-40 mesh) were physically mixed and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions of the catalyst were the same as those in Example 1. The reaction conditions were: hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) = 72.0 / 24.0 / 4.0 reaction gas, the catalyst bed temperature was controlled to be 240° C., the reaction pressure was 1 MPa, 2 MPa, 3 MPa, 5 MPa, 7 MPa, 9 MPa, and the volume space velocity range of the feed gas was 6000 mL / (g cat The experimental results are shown in Table 5.

[0087] Table 5:

[0088]

[0089] 240℃,SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4, and the operating time is 40h.

[0090] From the above test results, it can be seen that increasing the reaction pressure can simultaneously increase the CO2 conversion rate and methanol selectivity of the CuZnAlSi0.2 catalyst. When the reaction pressure is 9MPa, the CO2 conversion rate and methanol selectivity are as high as 18.2% and 92.5%, and the methanol yield reaches 16.8%.

[0091] Example 6: Tests at different reaction flow rates.

[0092] The CuZnAlSi0.2 catalyst is the same as in Example 2. The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor, and the test steps for the catalytic reaction performance were as follows:

[0093] 0.5 g CuZnAlSi0.2 (20-40 mesh) and 2.0 g quartz sand (20-40 mesh) were physically mixed and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions of the catalyst were the same as those in Example 1. The reaction conditions were: a reaction gas of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) = 72.0 / 24.0 / 4.0, the catalyst bed temperature was controlled to be 240°C, the reaction pressure was 3 MPa, and the volume space velocity range of the feed gas was 500 mL / (g cat ·h)、1000mL / (g cat ·h)、3000mL / (g cat ·h)、6000mL / (g cat ·h)、10000mL / (g cat ·h)、50000mL / (g cat The experimental results are shown in Table 6.

[0094] Table 6:

[0095]

[0096]

[0097] 3MPa, 240℃, H2 / CO2 / Ar=72 / 24 / 4, operating time is 40h.

[0098] From the above test results, it can be seen that increasing the reaction space velocity can improve the methanol selectivity of CuZnAlSi0.2 catalyst, but it will also cause a decrease in CO2 conversion rate. For example, when the space velocity is 500mL / (g cat ·h), the CO2 conversion rate reached 16.4% and the methanol selectivity was 79.8%; when the space velocity was 10000mL / (g cat When the CO2 conversion rate dropped to 13.2%, the methanol selectivity increased to 87.7%. cat ·h), CO2 conversion rate dropped to 7.2%, methanol selectivity was 92.2%. Combined with the actual methanol production, the space velocity was 3000~10000mL / (g cat h) is the appropriate reaction space velocity.

[0099] Example 7: Testing under different H2 / CO2.

[0100] The CuZnAlSi0.2 catalyst is the same as in Example 2. The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor, and the test steps for the catalytic reaction performance were as follows:

[0101] 0.5 g CuZnAlSi0.2 (20-40 mesh) and 2.0 g quartz sand (20-40 mesh) were physically mixed and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions of the catalyst were the same as those in Example 1. The reaction conditions were as follows: a certain proportion of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) reaction gas was introduced to make H2 / CO2=1, 2, 3, 5, 10, the catalyst bed temperature was controlled to be 240°C, the reaction pressure was 3 MPa, and the volume space velocity range of the feed gas was 6000 mL / (g cat The experimental results are shown in Table 7.

[0102] Table 7:

[0103]

[0104] 3MPa, 240℃, SV=6000mL / (g cat ·h), the running time is 40h.

[0105] From the above test results, it can be seen that with the increase of H2 / CO2 ratio, the CO2 conversion rate of CuZnAlSi0.2 catalyst can be improved at the same time, but the methanol selectivity will gradually decrease. When H2 / CO2 is 1, the CO2 conversion rate is 4.1% and the methanol selectivity is 87.9%; when H2 / CO2 is 10, the CO2 conversion rate rises to 15.8%, but the methanol selectivity drops to 69.8%. Therefore, H2 / CO2=3~5 is the appropriate gas ratio.

[0106] Example 8: Tests at different CO contents.

[0107] The CuZnAlSi0.2 catalyst is the same as in Example 2. The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor, and the test steps for the catalytic reaction performance were as follows:

[0108] 0.5 g CuZnAlSi0.2 (20-40 mesh) and 2.0 g quartz sand (20-40 mesh) were physically mixed and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions of the catalyst were the same as those in Example 1. The reaction conditions were as follows: a certain proportion of hydrogen / carbon dioxide / argon (H2 / CO2 / Ar) reaction gas was introduced to make H2 / CO2=3; and CO with a molar percentage of 0, 1, 2, 3, 5, and 10% was added to the reaction gas, the catalyst bed temperature was controlled to be 240°C, the reaction pressure was 3 MPa, and the volume space velocity range of the feed gas was 6000 mL / (g cat The experimental results are shown in Table 8.

[0109] Table 8:

[0110]

[0111] 3MPa, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4 / x (x is CO mol content), and the operating time is 40h.

[0112] From the above test results, it can be seen that the introduction of CO will reduce the CO2 conversion rate on the catalyst, but will increase the methanol selectivity. As the amount of CO introduced increases from 0 to 10 mol%, the CO2 conversion rate of the CuZnAlSi0.2 catalyst decreases from 14.5% to 5.5%, but the methanol selectivity increases from 85.1 to 95.5%. In general, the amount of CO introduced needs to be controlled at 0-2%.

[0113] Example 9: Catalyst life test.

[0114] The CuZnAl-1 catalyst is the same as in Example 1, and the CuZnAlSi0.2 catalyst is the same as in Example 2. The carbon dioxide hydrogenation reaction is tested on a fixed bed reactor, and the test steps for the catalytic reaction performance are as follows:

[0115] 0.5 g CuZnAlSi0.2 (20-40 mesh) and 0.5 g CuZnAl-1 catalyst were physically mixed with 2.0 g quartz sand (20-40 mesh), respectively, and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions and reaction conditions of the catalyst were the same as those in Example 1. The reaction results are shown in Tables 9 and 10.

[0116] Table 9:

[0117]

[0118]

[0119] CuZnAlSi0.2, 3MPa, 240℃, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4.

[0120] Table 10:

[0121]

[0122] CuZnAl-1, 3MPa, 240℃, space velocity 6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4.

[0123] Figure 1 and Figure 3 They are the in-situ reduction X-ray photoelectron spectroscopy (XPS) and carbon monoxide adsorption infrared spectrum of CuZnAl-1 catalyst respectively. Figure 2 and Figure 4 The in-situ reduction X-ray photoelectron spectroscopy (XPS) and carbon monoxide adsorption infrared spectrum of the CuZnAlSi catalyst are shown in Figure 1. The in-situ XPS and CO adsorption infrared spectrum show that the introduction of silicon dioxide is beneficial to strengthen the interaction between the copper metal and the support on the CuZnAl catalyst, inhibit the sintering of Cu metal during the reaction, and improve the stability of the catalyst. In addition, it also promotes the Cu on the catalyst δ+ Species formation. Due to Cu δ+ Species can stabilize CH3O * The introduction of silica effectively reduces the selectivity of CO on the copper-based catalyst and improves the selectivity of methanol.

[0124] At the same time, it can be seen from the above test results (Table 9 and Table 10) that the conversion rate of CO2 of CuZnAlSi0.2 catalyst is stable at ~14.4% and the methanol selectivity is ~85.0% in the 2000-hour life test. However, the CuZnAl-1 catalyst shows obvious deactivation in the 2000-hour life test, with the CO2 conversion rate dropping from 23.5% to 12.1% and the methanol selectivity dropping from 54.4% to 46.5%. Therefore, the introduction of silicon dioxide can improve the stability of the CuZnAl catalyst.

[0125] Comparative Example 1:

[0126] (1) Synthesis of copper-zinc-aluminum catalyst comparison sample

[0127] The CuZnAl-1 catalyst was synthesized by coprecipitation. 12.05g (0.050mol) copper nitrate trihydrate, 10.40g (0.035mol) zinc nitrate hexahydrate and 5.63g (0.015mol) aluminum nitrate nonahydrate were dissolved in 200mL deionized water to obtain aqueous solution A. 15.90g (0.15mol) sodium carbonate was dissolved in 200mL deionized water to obtain aqueous solution B. Aqueous solution A and aqueous solution B were simultaneously dripped into a beaker containing 200mL deionized water, and the temperature was kept at 60℃ and the stirring speed was kept at 700rpm. The dripping flow rate of solution A was controlled to be 3mL / min, and the dripping speed of aqueous solution B was adjusted, and the pH of the liquid in the beaker was kept in the alkaline range. After aging the obtained precipitate for 12h, it was washed with deionized water, filtered 6 times, and dried at 100℃ for 12h. The dried product was placed in a muffle furnace and calcined at 500° C. for 4 hours in air to obtain a copper-zinc-aluminum catalyst CuZnAl-1, in which the molar percentages of copper, zinc and aluminum were 50%, 35% and 15% respectively.

[0128] (1.2) CuZnAl-2 catalyst was synthesized by coprecipitation. 15.00 g (0.060 mol) of copper sulfate pentahydrate, 8.91 g (0.030 mol) of zinc nitrate hexahydrate and 1.51 g (0.010 mol) of aluminum chloride hexahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. Aqueous solution A and aqueous solution B were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted to keep the pH of the liquid in the beaker in the alkaline range. After aging the obtained precipitate for 12 h, it was washed with deionized water, filtered 6 times, and dried at 100 °C for 12 h. The dried product was placed in a muffle furnace and calcined at 500° C. for 4 hours in air to obtain a copper-zinc-aluminum catalyst CuZnAl-2, in which the molar percentages of copper, zinc and aluminum were 60%, 30% and 10% respectively.

[0129] (1.3) CuZnAl-3 catalyst was synthesized by coprecipitation. 10.00 g (0.040 mol) of copper sulfate pentahydrate, 2.97 g (0.010 mol) of zinc nitrate hexahydrate and 18.75 g (0.050 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. Aqueous solution A and aqueous solution B were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping flow rate of solution A was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted to keep the pH of the liquid in the beaker in the alkaline range. After aging the obtained precipitate for 12 h, it was washed with deionized water, filtered 6 times, and dried at 100 °C for 12 h. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours in air to obtain a copper-zinc-aluminum catalyst CuZnAl-3, in which the molar percentages of copper, zinc and aluminum were 40%, 10% and 50% respectively.

[0130] (1.4) CuZnAl-4 catalyst was synthesized by coprecipitation. 4.82 g (0.020 mol) of copper nitrate trihydrate, 14.85 g (0.050 mol) of zinc nitrate hexahydrate and 11.25 g (0.030 mol) of aluminum nitrate nonahydrate were dissolved in 200 mL of deionized water to obtain aqueous solution A. 15.90 g (0.15 mol) of sodium carbonate was dissolved in 200 mL of deionized water to obtain aqueous solution B. Aqueous solution A and aqueous solution B were simultaneously dripped into a beaker containing 200 mL of deionized water, and the mixture was heated at 60 °C and stirred at 700 rpm. The dripping rate of solution A was controlled to be 3 mL / min, and the dripping speed of aqueous solution B was adjusted to keep the pH of the liquid in the beaker in the alkaline range. After aging the obtained precipitate for 12 h, it was washed with deionized water, filtered 6 times, and dried at 100 °C for 12 h. The dried product was placed in a muffle furnace and calcined at 500°C for 4 hours in air to obtain a copper-zinc-aluminum catalyst CuZnAl-4, in which the molar percentages of copper, zinc and aluminum were 20%, 50% and 30% respectively.

[0131] The synthesis steps of the copper-zinc-aluminum catalyst are the same as those in Example 1. The carbon dioxide hydrogenation reaction is tested on a fixed bed reactor. The test steps for the catalytic reaction performance are as follows:

[0132] The four kinds of CuZnAl catalysts (20-40 mesh) synthesized above were loaded into a stainless steel reaction tube, and both ends were filled with quartz wool to maintain the bed height, and a fixed bed reactor was assembled; the reduction conditions and reaction conditions of the catalyst were the same as those in Example 1, and the reaction results are shown in Table 11.

[0133] Table 11:

[0134]

[0135] 3MPa, 240℃, SV=6000mL / (gcath), H2 / CO2 / Ar=72 / 24 / 4, TOS=40h.

[0136] Comparative Example 2:

[0137] The synthesis steps of CuZnAl-1 catalyst are the same as those in Example 1. 2.5 g CuZnAl-1 powder and 0.5 g white carbon black powder, or 2.5 g CuZnAl-1 powder and 0.5 g fine silica gel powder are physically mixed and named as CuZnAl-1-white carbon black or CuZnAl-1-fine silica gel.

[0138] The carbon dioxide hydrogenation reaction was tested on a fixed bed reactor. The test steps for the catalytic reaction performance are as follows:

[0139] (1) 0.5 g CuZnAl-1, or 0.6 g CuZnAl-1-white carbon black (20-40 mesh) or 0.6 g CuZnAl-1-fine silica gel and 2.0 g quartz sand (20-40 mesh) were physically mixed and loaded into a stainless steel reaction tube. Both ends were plugged with quartz wool to maintain the bed height, and a fixed bed reactor was assembled. The reduction conditions and reaction conditions of the catalyst were the same as those in Example 1. The reaction results are shown in Table 12.

[0140] Table 12:

[0141]

[0142] 3MPa, 240℃, SV=6000mL / (g cat ·h), H2 / CO2 / Ar=72 / 24 / 4, TOS=40h.

[0143] From the test results of the above examples and comparative examples, it can be seen that the physical introduction of silicon dioxide (i.e., physical mixing of silicon dioxide with CuZnAl catalyst) does not change the performance of CuZnAl catalyst, but the chemical introduction of silicon dioxide (i.e., introduction of silicon dioxide during the synthesis of CuZnAl catalyst) can effectively improve the stability, methanol selectivity and methanol yield of CuZnAl catalyst. This will provide great help for the industrial application of traditional copper-zinc-aluminum catalysts.

[0144] Finally, it should be noted that the above examples are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above examples, and many variations are possible. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a silica-modified copper-zinc-aluminum catalyst, characterized in that: The specific contents include: Take copper salt, zinc salt and aluminum salt, and dissolve them in deionized water to obtain solution A; take sodium carbonate, and dissolve it in deionized water to obtain solution B; take silicon salt or organic silicon, and dissolve it in deionized water or anhydrous ethanol to obtain solution C; under stirring conditions of 20 to 80° C., drop solution A, solution B and solution C into a beaker containing deionized water, and adjust the dropping speed of solution B to keep the pH value of the reaction solution in an alkaline range; The precipitate obtained by the reaction is aged for 2 to 24 hours, washed with deionized water, filtered, dried and calcined to obtain a copper-zinc-aluminum-silicon catalyst; the molar percentages of copper, zinc, aluminum and silicon in the copper-zinc-aluminum-silicon catalyst are 20% to 50%, 10% to 40%, 10% to 40% and 10% to 30%, respectively.

2. The method for preparing a silica-modified copper-zinc-aluminum catalyst according to claim 1, characterized in that: The copper salt, zinc salt and aluminum salt are one or more of nitrates, sulfates and chlorides corresponding to the elements copper, zinc and aluminum, respectively.

3. The method for preparing a silica-modified copper-zinc-aluminum catalyst according to claim 1, characterized in that: The silicon salt or organosilicon is one or more of sodium silicate, ethyl orthosilicate, dimethyldiethoxysilane and phenyltriethoxysilane.

4. The method for preparing a silica-modified copper-zinc-aluminum catalyst according to claim 1, characterized in that: The stirring speed is 200-2000 rpm, the dripping flow rates of solution A and solution C are both 1-20 mL / min, the temperature is controlled at 60-180° C. and the time is 4-48 h during drying; the calcination is carried out in a muffle furnace with air passing through, the temperature is controlled at 300-700° C. and the time is 2-12 h.

5. A method for using a silica-modified copper-zinc-aluminum catalyst, characterized in that: The silica-modified copper-zinc-aluminum catalyst is prepared by the preparation method of the silica-modified copper-zinc-aluminum catalyst according to any one of claims 1 to 4, specifically comprising: The silica-modified copper-zinc-aluminum catalyst is loaded into a fixed bed reaction device, reduced by a mixture of hydrogen and nitrogen with a hydrogen concentration of 5 to 99 mol% at 210 to 400° C., and then heated at a temperature of 200 to 300° C., a pressure of 1 to 9 MPa, and a space velocity of 500 to 50000 mL / (g cat ·h), introducing reaction gas to realize catalytic hydrogenation to produce methanol; the molar ratio of H2 to CO2 in the reaction gas is (1-10):

1.

6. The method for using a silica-modified copper-zinc-aluminum catalyst according to claim 5, characterized in that: If it is necessary to add CO to the reaction gas, the molar percentage of CO to the reaction gas is 0-10%.

Citation Information

Patent Citations

  • Preparation method of copper-zinc-aluminum-molecular sieve catalyst for catalyzing CO2 hydrogenation to prepare methanol

    CN116393160A

  • Copper-based catalyst as well as preparation method and application thereof

    CN118079932A

  • Copper base catalyst in use for preparing hydrogen by reforming vapor of methanol and preparation method

    CN1562472A